2009
DOI: 10.1111/j.1540-8159.2008.02286.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality and Hospitalization for Cardiac Causes in Patients with Heart Failure and Nonischemic Heart Disease: A Subanalysis of the ALPHA Study

Abstract: In an unselected population of patients with HF and nonischemic heart disease, a reduced exercise capacity, large LV end-diastolic diameter, low systolic blood pressure, and hemoglobin were correlated with long-term all-cause mortality or hospitalization for cardiac causes. These observations may help stratifying and tailoring the treatment of patients with HF and nonischemic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Prognostic factors of HF include LVEF, NYHA class, older age, male sex, low exercise capacity (6MWT), low systolic blood pressure, low hemoglobin, etc. [ 19 , 20 , 21 ]. Several clinical prediction models have been created for HF (The Seattle Heart Failure Model, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors of HF include LVEF, NYHA class, older age, male sex, low exercise capacity (6MWT), low systolic blood pressure, low hemoglobin, etc. [ 19 , 20 , 21 ]. Several clinical prediction models have been created for HF (The Seattle Heart Failure Model, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, large LVIDd has been reported as an independent predictor for all-cause mortality or hospitalization for cardiac causes [32]. We have in an earlier study found that ambulatory ST segment depression, as a measure of ischemic heart disease (IHD), was associated with lower cognitive function, both visuospatial and verbal [14].…”
Section: Discussionmentioning
confidence: 99%
“…253 Outras variáveis clínicas associadas a maior risco de eventos arrítmicos nesta população são o não uso de betabloqueadores e a pressão arterial sistólica. 254,255 Exames laboratoriais, como hemoglobina, ácido úrico e peptídio natriurético atrial (BNP), aparecem como preditores de mortalidade e eventos arrítmicos em alguns estudos. 256 A redução da FEVE é considerada o principal fator de risco para MSC e mortalidade total em pacientes com IC.…”
Section: Miocardiopatia Não Isquêmicaunclassified